2020
DOI: 10.1007/s00392-020-01645-6
|View full text |Cite
|
Sign up to set email alerts
|

Midregional pro atrial natriuretic peptide: a novel important biomarker for noise annoyance-induced cardiovascular morbidity and mortality?

Abstract: Background Environmental noise exposure has been associated with increased cardiovascular morbidity and mortality. Recently, noise annoyance was shown to induce atrial fibrillation, which was accompanied by significantly increased levels of midregional pro atrial natriuretic peptide (MR-proANP). Therefore, the aim of the present study was to analyze the association between noise annoyance, MR-proANP, incident cardiovascular events, and all-cause mortality. Methods Levels of MR-proANP were measured in the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…We followed the methods of Hahad et al ( 16 ). In brief, the GHS is a population-based, prospective single-center cohort study from Mid-Western Germany including 15,010 subjects (aged 35–74 years) of the baseline examination performed from April 2007 to April 2012 at the University Medical Center Mainz, Germany.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We followed the methods of Hahad et al ( 16 ). In brief, the GHS is a population-based, prospective single-center cohort study from Mid-Western Germany including 15,010 subjects (aged 35–74 years) of the baseline examination performed from April 2007 to April 2012 at the University Medical Center Mainz, Germany.…”
Section: Methodsmentioning
confidence: 99%
“…Fasting blood and anthropometric data were collected and routine laboratory methods were used for measurements of blood glucose, lipids, and cardiovascular risk factors. Detailed information about clinical and laboratory examinations as well as exact definition of included variables have been reported previously ( 16 , 20 , 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…All individuals provided written informed consent before study enrolment and the study procedures are conducted in line with the principles outlined in the Declaration of Helsinki and the recommendations for Good Epidemiological Practice. The rationale and design of the GHS were published previously 17 , 18 . Data acquisition was performed using a highly standardized investigational protocol at the study platform.…”
Section: Methodsmentioning
confidence: 99%
“…There was no correlation between those who responded to be annoyed by or sensitive to noise, implying that the effects were not via an emotional pathway and that noise-induced damage would occur independent of cognition. Conversely, population-based cohort studies clearly demonstrated a dose-dependent increase of prevalent atrial fibrillation [137], accompanied by increased midregional pro-atrial natriuretic peptide levels [138], a cardiac hormone that mirrored endothelial activation and predicted future cardiovascular events, in response to annoyance due to different noise sources, including traffic noise. These effects could possibly be impactful on future cardiovascular events [16,139].…”
Section: Oxidative Stress and Inflammation By Traffic Noise Exposurementioning
confidence: 99%